2014
DOI: 10.1007/s10753-014-9917-y
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Factors of Avascular Necrosis in Patients with Systemic Lupus Erythematosus: a Meta-analysis

Abstract: The aim of this study was to determine the risk factors for avascular necrosis (AVN) in patients with systemic lupus erythematosus (SLE). Four electronic databases (PubMed, EMBASE, Ovid, and Science Direct) were searched for. The search was performed to identify the articles as to SLE with AVN before September 2013. The clinical and laboratory data were extracted, and a meta-analysis was performed to identify the risk factors for AVN in patients with SLE. Publication bias was assessed with funnel plot and Egge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 29 publications
2
25
0
1
Order By: Relevance
“…In agreement with that, proteinuria has recently been reported to be a predictor of pericarditis [30]. The risk of AVN with renal disease and hypertension was previously established [31], and it is noticed in the current work that AVN is a predictor of pericardial effusion as well. In this context, the protective effect of HCQ against metabolic disorders in SLE [32, 33] seems to modify the risk of pericardial diseases.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with that, proteinuria has recently been reported to be a predictor of pericarditis [30]. The risk of AVN with renal disease and hypertension was previously established [31], and it is noticed in the current work that AVN is a predictor of pericardial effusion as well. In this context, the protective effect of HCQ against metabolic disorders in SLE [32, 33] seems to modify the risk of pericardial diseases.…”
Section: Discussionsupporting
confidence: 88%
“…Another one 70 did not find a strong correlation between aPL and the occurrence of ON. Thus, the true character of the association between aPL and ON in SLE is not clear and seems to be, at best, weak.…”
Section: Rheumatologymentioning
confidence: 89%
“…The additive effects of multidrug treatment in PV patients should not be underestimated. Not only do corticosteroids have a significantly deleterious impact on bone metabolism, many studies have also found cytotoxic drugs to be risk factors for AVN . Bisphosphonate‐induced vitamin D deficiency may also contribute to the occurrence of AVN, as reported in ONJ and pediatric AVN cases .…”
Section: Discussionmentioning
confidence: 99%